Factors Influencing the Implementation of Digital Advance Care Planning: Qualitative Interview Study - Bradshaw, Andy; Birtwistle, Jacqueline; Evans, Catherine J; Sleeman, Katherine E; Richards, Suzanne; Foy, Robbie; Millares Martin, Pablo; Carder, Paul; Allsop, Matthew J; Twiddy, Maureen (Journal of medical Internet research, 2024)
Palliative care aims to improve the quality of life for people with life-limiting illnesses. Advance care planning conversations that establish a patient's wishes and preferences for care are part of a person-centered approach. Internationally, electronic health record systems are digital interventions used to record and share patients' advance care plans across health care services and settings. They aim to provide tools that support electronic information sharing and care coordination. Within the United Kingdom, Electronic Palliative Care Coordination Systems (EPaCCS) are an example of this. Despite over a decade of policy promoting EPaCCS nationally, there has been limited implementation and consistently low levels of use by health professionals. The aim of this study is to explore the factors that influence the implementation of EPaCCS into routine clinical practice across different care services and settings in 2 major regions of England. A qualitative interview study design was used, guided by Normalization Process Theory (NPT). NPT explores factors affecting the implementation of complex interventions and consists of 4 primary components (coherence, cognitive participation, collective action, and reflexive monitoring). Health care and social care practitioners were purposively sampled based on their professional role and work setting. Individual web-based semistructured interviews were conducted. Data were analyzed using thematic framework analysis to explore issues which affected the implementation of EPaCCS across different settings at individual, team, organizational, and technical levels. Participants (N=52) representing a range of professional roles were recruited across 6 care settings (hospice, primary care, care home, hospital, ambulatory, and community). In total, 6 themes were developed which mapped onto the 4 primary components of NPT and represented the multilevel influences affecting implementation. At an individual level, these included (1) EPaCCS providing a clear and distinct way of working and (2) collective contributions and buy-in. At a team and organizational level, these included (3) embedding EPaCCS into everyday practice and (4) championing driving implementation. At a technical level, these included (5) electronic functionality, interoperability, and access. Breakdowns in implementation at different levels led to variations in (6) confidence and trust in EPaCCS in terms of record accuracy and availability of access. EPaCCS implementation is influenced by individual, organizational, and technical factors. Key challenges include problems with access alongside inconsistent use and engagement across care settings. EPaCCS, in their current format as digital advance care planning systems are not consistently facilitating electronic information sharing and care coordination. A redesign of EPaCCS is likely to be necessary to determine configurations for their optimal implementation across different settings and locations. This includes supporting health care practitioners to document, access, use, and share information across multiple care settings. Lessons learned are relevant to other forms of digital advance care planning approaches being developed internationally.